İSKEMİK STROKTA ELEKTROKARDİYOGRAFİK BULGULAR - İNCE, Birsen and ÇELİK, Yahya and BİNGÖL, Hülya and HARMANCI, Hande and DENKTAŞ, Hayrünnisa (Cerrahpaşa Medical Journal, 2019)
Background and Design. The prognosis of stroke has been claimed to be worsened at the presence of electrocardiographic findings. An association with mortality and ECG finding has not been well documented in patients with stroke. This case control study covers 87 consecutive patients with ischemic stroke and 87 control patients without stroke seen in any inpatient clinic other than cardiology between October 1995 June 1996. Results. There was no difference between the patient and control groups in terms of sex and age. In the case of ischemic stroke, ECG changes were identified in 62.1 %, whereas the rate was 29.9% in the control group. The difference was statistically significant (Odds ratio, 3.84; 95% confidence interval, 1.95 to 7.60, p<0.0001). The mostly seen ECG finding was myocardial ischemia. Case fatality rate in all patients after 6 months of follow up was 29.9%. The fatality rates of the patients with and without ECC changes (38.9% and 15.2% respectively) were significantly different (p<0.05). Conclusion. Cardiac consequences of stroke are likely to contribute to the stroke mortality. Patients with acute stroke should receive continuous cardiac monitoring until the cardiac problem and ECG findings have resolved.